2020
DOI: 10.1186/s13023-020-01506-5
|View full text |Cite|
|
Sign up to set email alerts
|

A Germany-wide survey study on the patient journey of patients with hereditary angioedema

Abstract: Background: Hereditary angioedema (HAE) is a rare genetic disease and characterized by clinical features such as paroxysmal, recurrent angioedema of the skin, the gastrointestinal tract, and the upper airways. Swelling of the skin occurs primarily in the face, extremities and genitals. Gastrointestinal attacks are accompanied by painful abdominal cramps, vomiting and diarrhea. Due to the low prevalence and the fact that HAE patients often present with rather unspecific symptoms such as abdominal cramps, the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
(22 reference statements)
5
17
0
Order By: Relevance
“…Data from the Icatibant Outcome survey show an average diagnostic delay of 23.9 years in the >65-year-old age-group compared to 4.8 years in the <65-year-old group [31]. Recent data from Germany show an average diagnostic delay of 18.1 years, which increases to 22.9 years in 60-79-year-old patients and to 38.5 years in the ≥80-year-old group [30].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Data from the Icatibant Outcome survey show an average diagnostic delay of 23.9 years in the >65-year-old age-group compared to 4.8 years in the <65-year-old group [31]. Recent data from Germany show an average diagnostic delay of 18.1 years, which increases to 22.9 years in 60-79-year-old patients and to 38.5 years in the ≥80-year-old group [30].…”
Section: Discussionmentioning
confidence: 97%
“…Other study groups reported an average diagnostic delay of 8.5 years with up to 65% of patients receiving at least 1 misdiagnosis and 24% reporting dispensable medical interventions while averagely consulting 4.4 physicians until HAE was correctly diagnosed [27][28][29]. A study by Magerl et al [30] shows that up to 80% of misdiagnosed HAE patients also receive a pharmaceutical or interventional mistreatment. Comparable to our findings, other study groups have described a significantly longer diagnostic delay in elder patients [30,31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, while medical students chose almost all the indicated specializations from the list more often than their already professionally active colleagues, the physicians interviewed in this study indicated the option ‘other specializations’ more frequently than the students did. This difference is especially surprising when we consider the significant contribution of family physicians in the diagnosis of RDs [ 42 , 50 ]. Thus, while we may wonder whether these differences result from physicians’ post-graduation experiences, there is no doubt that such a difference does exist.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic angioedema and appendicitis are the most frequent causes related to subcutaneous and submucosal edema, respectively ( 56 ). The delay on diagnosis is still a burden for HAE patients ( 57 , 58 ). These findings suggest that additional investment must be done to improve the awareness of HAE.…”
Section: Challenges Faced To Reach Diagnosismentioning
confidence: 99%